Soft Power Strategies for PM2.5 Risk Communication in Border Regionsommunication in Border Regions - ฤทธิ์ฤาชัย สุดคนึง; บุญชุติมา สมิทธิ์; จันทร์แดง พิทักษ์พงษ์; วิริยะ ว่าน; คุปต์กานต์ สุนันทา; สุมะนะ เอกะสิทธิ์ (Journal of Health Science of Thailand, 2025)
Particulate matter 2.5 mm. (PM2.5) pollution poses significant environmental and public health challenges in Thailand’s border regions, where local and transboundary sources exacerbate air quality problems. This study investigated the integration of soft power principles into PM2.5 risk communication strategies through a mixed-methods approach conducted across six border provinces. The research involved 353 participants, including public health officers, village health volunteers, and community members, examining knowledge levels, communication practices, and cultural adaptation needs. Quantitative analysis revealed high levels of technical knowledge among health workers (93.8% correctly identifying PM2.5 characteristics), though confidence in communication skills varied significantly, particularly in managing public misconceptions (Mean=3.60, SD=0.736). Strong correlations emerged between community cooperation and managing public doubts (r=0.785, p<0.01), underscoring trust-building’s importance. Qualitative findings elucidated that these doubts often stemmed from economic constraints, feelings of helplessness regarding transboundary pollution, and inconsistent regulatory enforcement. Qualitative findings also emphasized the crucial role of cultural sensitivity and economic considerations in message reception and behavioral change. The study identified significant gaps between technical understanding and effective community engagement. Digital media presented both an opportunity (high demand for training, Mean=3.97, SD=0.794) and challenges, with implementation barriers in resource-limited settings. Qualitative data highlighted the need for locally tailored digital content and culturally appropriate solutions to overcome these barriers. The research contributes to theoretical understanding by demonstrating specific applications of soft power in environmental health communication and identifying mechanisms through which cultural factors influence message effectiveness. These findings support the development of culturally adapted communication strategies that integrate traditional and modern approaches while maintaining strong community involvement. Recommendations include strengthening cultural competency training for health workers, developing integrated communication strategies, and enhancing cross-border cooperation mechanisms. Future research directions should examine long-term impacts of culturally adapted communication strategies and investigate emerging technologies in supporting cultural adaptation of health messages.